Prevalence of Glucose-6-Phosphate Dehydrogenase Deficiency among Neonates with Severe Neonatal Hyperbilirubinemia: A Cross-Sectional Study from Assam - Atiqur Rahman; Indira Das; Nazrul Islam Barbhuiyar (Global Journal of Medicine and Public Health, 2024)
Background Hyperbilirubinemia is a common issue in neonates, with jaundice affecting a significant proportion of both term and preterm infants. While most cases of neonatal jaundice are benign, a subset requires intervention. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a notable cause of pathological jaundice that can lead to severe hyperbilirubinemia and neurological complications. So, this study aimed to determine the prevalence of G6PD deficiency among neonates with severe hyperbilirubinemia.